Negative interest rate policies: Sources and implications - Carlos Ó. Arteta; M. Ayhan Kose; Marc Stocker; Temel Taskin (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
Against the background of continued growth disappointments, depressed inflation expectations, and declining real equilibrium interest rates, a number of central banks have implemented negative interest rate policies (NIRP) to provide additional monetary policy stimulus over the past few years. This paper studies the sources and implications of NIRP. We report four main results. First, monetary transmission channels under NIRP are conceptually analogous to those under conventional monetary policy but NIRP present complications that could limit policy effectiveness. Second, since the introduction of NIRP, many of the key financial variables have evolved broadly as implied by the standard transmission channels. Third, NIRP could pose risks to financial stability, particularly if policy rates are substantially below zero or if NIRP are employed for a protracted period of time. Potential adverse consequences include the erosion of profitability of banks and other financial intermediaries, and excessive risk taking. However, there has so far been no significant evidence that financial stability has been compromised because of NIRP. Fourth, spillover implications of NIRP for emerging market and developing economies are mostly similar to those of other unconventional monetary policy measures. In sum, NIRP have a place in a policy maker's toolkit but, given their domestic and global implications, these policies need to be handled with care to secure their benefits while mitigating risks.
Keywords: E52; E58; E60; 330; unconventional monetary policy; quantitative easing; bank profitability; financial stability; negative yields; event study; emerging markets; developing countries